Studies of nanoconstrictions, nanowires and Fe3O4 thin Films electrical conduction and magnetic properties. Fabrication by focused electron/ion beam - Fernandez-Pacheco, Amalio (Springer, 2011)
This work constitutes a detailed study of electrical and magnetic properties in nanometric materials with a range of scales: atomic-sized nanoconstrictions, micro- and nanowires and thin films. Firstly, a novel method of fabricating atomic-sized constrictions in metals is presented; it relies on measuring the conduction of the device while a focused-ion-beam etching process is in progress. Secondly, it describes wires created by a very promising nanolithography technique: Focused electron/ion-beam-induced deposition. Three different gas precursors were used: (CH₃)₃Pt(CpCH₃), W(CO)₆ and Co₂(CO)₈. The thesis reports the results obtained for various physical phenomena: the metal-insulator transition, superconducting and magnetic properties, respectively. Finally, the detailed magnetotransport properties in epitaxial Fe₃O₄ thin films grown on MgO (001) are presented. Overall, the new approaches developed in this thesis have great potential for supporting novel technologies.